How CrRLK1L Receptor Complexes Perceive RALF Signals. (November 2019) - Ge, Zengxiang; Dresselhaus, Thomas; Qu, Li-Jia
Abstract : RALFs are secreted peptides that are perceived by various CrRLK1L–LRE/LLG receptor complexes. The mechanistic basis of this perception has now been elucidated showing that the co-receptor LLG binds RALF23 to nucleate a FER receptor complex. This interaction likely occurs in other tissues where RALFs meet CrRLK1L receptors and LRE/LLG co-receptors.